2013
DOI: 10.1227/neu.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Generalized Q-Sampling Imaging and Diffusion Tensor Imaging in the Preoperative Visualization of the Nerve Fiber Tracts Within Peritumoral Edema in Brain

Abstract: GQI can visualize the tracts in the peritumoral edema of cerebral tumors better than DTI. Although GQI has many limitations, its future in the preoperative guidance of brain tumor lesions is promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 25 publications
3
76
0
Order By: Relevance
“…Some groups also attempted to address this challenge in the imaging/scanner level with other fiber orientation estimation/modeling methods. Zhang et al (2013) compared generalized q-sampling based tractography with DTI-based WM mapping in edematous regions. They demonstrated that DTI-based tractography missed several fiber tracts in 5 cases in comparison with those from generalized q-sampling imaging (GQI) data.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups also attempted to address this challenge in the imaging/scanner level with other fiber orientation estimation/modeling methods. Zhang et al (2013) compared generalized q-sampling based tractography with DTI-based WM mapping in edematous regions. They demonstrated that DTI-based tractography missed several fiber tracts in 5 cases in comparison with those from generalized q-sampling imaging (GQI) data.…”
Section: Discussionmentioning
confidence: 99%
“…As we demonstrated in our study, clinical diffusion data of around 30 directions at a b-value of 1000 s/mm 2 is adequate for two-tensor UKF tractography. Another study by Zhang et al [27] showed that generalized q-sampling imaging can visualize the tracts in the peritumoral edema of cerebral tumors better than DTI. McDonald et al [28] also demonstrated that restriction spectrum imaging can be used to improve the quantification and visualization of white matter tracts in regions of peritumoral edema.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of mass lesions, an abnormal trajectory of a fiber may be either technical in origin or real. 1,23 Despite the improved ability of the advanced techniques 22,50 to depict white matter tracts in the perilesional edematous zone, a careful interpretation of the qualitative data should be carried out with a sound knowledge of the loco-regional neuroanatomy to facilitate safer surgical planning. Relevant to the quantitative analysis in the longitudinal studies is the variability in the parameters, such as QA, that can occur across the scanning sessions.…”
Section: Tractography Versus Diffusion Connectometry Approach: Generamentioning
confidence: 99%